A Templar's apprentice - Black, Kat. (New York : Scholastic, 2009)
While trying to harness his power for prophetic visions, a fourteenth-century Scottish boy joins a Templar knight on his sacred quest to unearth an ancient relic.
700
Accelerated Reader AR
Keywords: Templars -- History -- Juvenile fiction; Templars -- Fiction; Knights and knighthood -- Fiction; Middle Ages -- Fiction; Clairvoyance -- Fiction; Apprentices -- Fiction; Adventure and adventurers -- Fiction